Did the metal object hit the cornea? A case report of penetrating ocular injury with embedded foreign body: Poster Presentation - Case Report - Resident - AGUNG NUGROHO; Dearaini; Annisa Windyani; Susantono, Diannisa Paramitha; Pangestika, Rishka; Laksmita, Yulinda Arty; Widyawati, Syska; Adriono, Gitalisa Andayani (Majalah Oftalmologi Indonesia, 2023)
Introduction : Penetrating ocular injury with IOFBs may cause severe ocular damage. We demonstrate the diagnostic and treatment approach in a case of scleral laceration with a large IOFB. Case Illustration : A-24-year-old male presented with a rusty segment of fence wire, sized 15x11 mm, embedded near the nasal corneal margin of the right eye. Upon initial examination the vision was 6/9 with normal IOP. The object obstructed the view of the entry site, therefore corneal wound was suspected. CT scan showed penetrating metal object without posterior segment involvement. Anti-tetanus injection, topical and oral levofloxacin were given. He underwent exploration, foreign body removal and repair surgery. During surgery, the wound was revealed as a scleral laceration, 4 mm from nasal limbus. One day post-operative, vision was 6/20. A 0.1 mm hypopyon was found, along with fibrin at nasal vitreous. Oral and topical corticosteroids were given, and hypopyon disappeared the next day. One week after surgery, vision improved to 6/7.5, with clear vitreous and normal retina. Discussion : Ocular injuries with large IOFBs can hinder clinical examination. Corneal entry wound should be ruled out, due to potential permanent damage to visual axis. CT scan was helpful in assessing the depth of object penetration. The object was removed successfully, with no damage to the cornea and retina. Anti-tetanus, antibiotics and corticosteroids were able to control infection and inflammation. Conclusion : Large IOFBs which do not affect the visual axis, can be managed with successful outcome, by prompt removal and repair of the entry wound, and control of infection and inflammation.